Determinan Mutu Belajar Mahasiswa Pendidikan Akuntansi Akibat Covid-19 - Nisa Fardani; Supri Wahyuning Utomo; Nur Wahyuning Sulistyowati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
This study aims to partially test the effect of e-learning and motivation on the learning quality of UNIPMA Accounting Education students due to Covid-19. This type of research is quantitative research with data collection techniques using questionnaires. This research was conducted on students of Class 2017, 2018, and 2019 with a population of 78 respondents with a saturated sample of 78 student respondents. The results prove that the learning quality of UNIPMA Accounting Education students as a result of Covid-19 is positively and significantly affected by e-learning, namely with the opportunity to work together, through the availability of software so as to facilitate the learning process simultaneously without any constraints on distance. In addition, motivation also affects the quality of student learning, namely with the ambition and desire to succeed students in improving their competencies.